Motivating and Critical Success Factors in the ISO 9001:2015 Implementation of the Provincial Government of Bulacan - Santos, Cecille de Guzman (Future Science / FSH-PH Publications, 2022)
Quality is an essential performance measure in both the private and public sector. The adoption of a Quality Management System (QMS)/ISO 9001:2015 standard is a strategic decision that can help improve an organization’s overall performance. This study aimed to assess the ISO 9001:2015 implementation of the Provincial Government of Bulacan in terms of the selected critical success factors and workforce level of motivation and be able to provide recommendations for improvement. This study used the quantitative, non-experimental, descriptive research design, employing survey and correlational approaches. A qualitative approach through qualitative interview was also utilized to capture the implementation strategies. The overall analysis revealed that 8 motivating factors obtained a low level of relationship with all of the selected critical success factors while the 9th motivating factor, Recognition and Feedback Received obtained a high level of relationship with 7 critical success factors indicating that Recognition and Feedback Received can affect the implementation of QMS tasks in terms of the critical success factors. Findings also showed that there is an opportunity in trainings. Leaders can identify training needs to support a more effective QMS implementation. Furthermore, the Provincial Government of Bulacan can revisit and strengthen the performance evaluation process as this can help meet the upper-level self-actualization needs of employees. A quality program with the suggested action plan has also been recommended towards overall performance improvement.